In vitro and in vivo antibacterial activities of E1077, a novel parenteral cephalosporin with a broad antibacterial spectrum. - Hata, K (1992)
E1077 is a new injectable cephalosporin with a broad spectrum of antibacterial activity against gram-positive and gram-negative bacteria, including staphylococci and Pseudomonas aeruginosa. The in vitro activities of E1077 against clinical isolates of methicillin-susceptible Staphylococcus aureus (MIC of E1077 for 90% of the strains tested [MIC90], 0.78 microgram/ml) and methicillin-resistant S. aureus (MIC90, 50 micrograms/ml) were similar to those of cefpirome and flomoxef. Against Enterococcus faecalis (MIC90, 6.25 micrograms/ml), E1077 was the most active of the drugs tested and four times more active than cefpirome. The MIC90S of E1077 for streptococci, Haemophilus influenzae, and Neisseria gonorrhoeae ranged from 0.05 to 0.78 microgram/ml; E1077 was similar in activity to cefpirome. E1077 inhibited 90% of most species of the family Enterobacteriaceae at concentrations of less than or equal to 1.56 micrograms/ml, with the exception of Serratia marcescens and Proteus vulgaris (12.5 micrograms/ml). The activity of E1077 against P. aeruginosa (MIC90, 6.25 micrograms/ml) was comparable to that of ceftazidime. In vivo activity was evaluated with systemic infections in mice. E1077 showed a protective effect against systemic infections by gram-positive or gram-negative bacteria, as reflected by its in vitro activity. The protective effects of E1077 were higher than those of cefpirome against S. aureus and P. aeruginosa infections and similar to those of cefpirome against other bacterial infections. Morphological studies using differential interference and phase-contrast microscopy showed that low concentrations of E1077 caused swelling of S. aureus and spheroplast and bulge formation in P. aeruginosa. In general, the antibacterial profile of E1077 is similar to that of cefpirome.